An exploration of the concept and practice of patient-centered care in medical education in Pakistan - Afifa Tabassum; Usman Mahboob; Syeda Kauser Ali (Pakistan Journal of Medical Sciences, 2026)
Objectives: To explore current understanding of patient centered care (PCC), its teaching and assessment practices and perceived factors influencing PCC learning in undergraduate and postgraduate medical education within a traditional cultural context. Methodology: An exploratory qualitative descriptive study was conducted from January to September 2024 in public sector hospitals in different provinces of Pakistan. Data was collected through focus group discussions with interns and residents of medicine, surgery and pediatrics selected through purposive sampling. Actor Network Theory informed data analysis and thematic analysis done using Braun and Clarke method. Results: Six focus groups were held with 33 participants in total. Four main themes and 14 subthemes emerged from analysis: Comprehending Patient-Centered Care, Teaching and Learning Practices, Influencing Factors, and Practice Implications. The central point highlighted was treating the patient as a whole, involving them in their care and giving consideration to personal values and preferences. Some PCC skills identified were technical expertise, communication skills, professionalism and understanding patient’s culture. Current teaching practices were theoretical with limited practical training with insufficient assessment. Curriculum, Faculty, Service, Personal and Patient-related factors were recognized as influencing factors. Conclusion: This study provides insights into learners’ perspectives and current teaching and assessment of patient-centered care within Pakistani context. The study highlights that to achieve the goal of trained workforce, changes in teaching and assessment practices, curriculum design and policy development at both institutional and national level are required while taking into account the sociocultural context. Addressing these factors could enhance preparation of future healthcare professionals to deliver holistic, patient-centered care.